ANALISIS YURIDIS PENGENAAN PASAL PENCEMARAN NAMA BAIK DAN CYBERBULLYING DALAM KASUS PENYEBARAN DATA PRIBADI OLEH FINTECH LENDING - Mieke Aprilia Utami; Sri Ridma Ramadhani; Suriyadi Suriyadi; Ahmad Murjani (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The practice of debt collection in peer-to-peer lending (fintech lending) in Indonesia is often characterized by digital intimidation and misuse of personal data, violating the constitutional rights of customers. This study aims to empirically examine the effectiveness of defamation articles in the ITE Law (Electronic Information and Transactions Law) and protection instruments in the PDP Law (Personal Data Protection Law) on the guarantee of customers' digital dignity protection. This study employs a quantitative method with a juridical-empirical approach. Data were collected via questionnaires from 100 fintech users selected using purposive sampling technique and analyzed using multiple linear regression. The results indicate that both regulations simultaneously have a positive and significant effect on customer protection, with a contribution of influence (R2) of 58.2%. Partially, the PDP Law was found to have a more dominant impact (β = 0.452) compared to the ITE Law (β = 0.284), indicating that customers feel more protected through preventive data governance mechanisms than reactive criminal approaches. This study concludes that although regulations are on the right track, law enforcement effectiveness is still hindered by a gap of 41.8%, influenced by the complexity of proving mens rea and inter-institutional bureaucracy. Therefore, the implementation of the strict liability principle for fintech operators is recommended to mitigate the risk of cyberbullying in the future.